CHANGES IN THE DIVERSITY OF TURTLES (TESTUDINATA) IN SOUTH AMERICA FROM THE LATE TRIASSIC TO THE PRESENT (Ameghiniana, 2018)
Recent advances in the fossil record, anatomy, and evolutionary history of South American turtles allow a thorough analysis of their changes in diversity, as well as to identify several major extinction events. The history of turtles in South America starts with stem turtles surviving in the southwestern margin of the Pangea. With the onset of the breakup of Pangea in the Middle Jurassic, turtles begin to diversify, giving rise to the main South American turtle clades, some of which survive until present. The first peak of diversity was achieved in the Early Cretaceous, given by basal members of Pelomedusoides, Pan-Chelidae, and Meiolaniformes. A first extinction event is recognized in the end of the Early Cretaceous, affecting mainly the pelomedusoids in northern latitudes and coinciding with the final separation of South America from Africa. Although a general trend of diversification was obtained for most of the Mesozoic, chelids registered extintion events during the middle to Late Jurassic, and posteriorly the clade is only represented by its crown group members. The K–Pg boundary mass extinction affected the thriving turtle communities deeply in South America by reducing their diversity in half. The effect of this extinction is noted in all clades and latitudes, although turtles with their distributions more extended towards the north (e.g., Pelomedusoides) were more affected. Reduction of diversity continued on the aftermath of the K–Pg extinction, roughly until the middle Eocene and the final isolation of South America from Antarctica. In this “new” continent, the surviving turtles continued to decrease on their diversity, up to an injection of biodiversity from Africa, with the arrival of tortoises, which helped to recover the diversity levels to higher values. The Andean uplift in Late Oligocene–Early Miocene and the associated climate and habitat changes posed new problems for the turtles and tortoises of the continent, but they continued to rise and expand. New injections of biodiversity took place at the end of the Neogene with the Great American Biotic Interchange, as novel clades reached South America from the North. The modern biodiversity of South American turtles took its final shape only during the last million years.